Brain Asymmetry of Structure And/Or Function - Lesley J. Rogers (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
This edited book brings together research reports on the asymmetry of brain function in various species, including humans, dogs, birds, lizards and bees. As shown in a wide range of species, and, as we now know, not solely in humans, the left and right sides of the brain process information in different ways and control different responses or patterns of behaviour. Since this discovery, many new methods have become available to reveal the processes involved in the development, function and evolution of this important attribute of the brain. Chapters consider the evidence for asymmetry of sensory receptors, left-right differences in information processing and asymmetrical control of behaviour. The latter includes lateralization of bird song and use of the magnetic compass in navigation. Other chapters report studies on handedness, hemispheric asymmetries in emotional processing and perception of symmetry in humans. The importance of the degree, or strength, of asymmetry is discussed and the conclusion is that asymmetry of the brain enhances its efficiency. Other chapters provide evidence that early experience influences the development of asymmetry. All of the contributors have strong backgrounds in research and they discuss up-to-date discoveries on lateralized brain and behaviour.